2018
DOI: 10.1007/s11307-018-1278-8
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]PSMA PET/CT Improves Initial Staging and Management Plan of Patients with High-Risk Prostate Cancer

Abstract: [Ga]PSMA PET/CT is an invaluable imaging modality in the assessment of primary high-risk PCa with great potential for the detection of lymph node spread and bone metastases that would impact the management plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 23 publications
0
25
1
1
Order By: Relevance
“…Six publications investigating the impact of PSMA-PET on management were published between 2018 and 2019 including a total of 396 patients, showing a range of management change from 21 to 52% [3,[8][9][10][11][12]. PSMA-PET was considered useful for improved patient selection for focal therapies, or to change therapy modalities based on the PET findings as shown also in a study from our group that found a change in management in 27% of patients based on the staging PSMA-PET [10,13].…”
Section: Introductionmentioning
confidence: 81%
“…Six publications investigating the impact of PSMA-PET on management were published between 2018 and 2019 including a total of 396 patients, showing a range of management change from 21 to 52% [3,[8][9][10][11][12]. PSMA-PET was considered useful for improved patient selection for focal therapies, or to change therapy modalities based on the PET findings as shown also in a study from our group that found a change in management in 27% of patients based on the staging PSMA-PET [10,13].…”
Section: Introductionmentioning
confidence: 81%
“…Prostate cancer is the most common solid malignancy in men and the third leading cause of cancer-related mortality in the western world (1). There is strong emerging evidence to suggest that using positron emission tomography (PET) probes that target prostate-specific membrane antigen (PSMA) can improve diagnostic accuracy and management of patients with prostate cancer (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is the most common solid malignancy in men and the third leading cause of cancer-related mortality in the western world (1). There is strong emerging evidence to suggest that using positron emission tomography (PET) probes that target prostate-specific membrane antigen (PSMA) can improve diagnostic accuracy and management of patients with prostate cancer (1)(2)(3)(4)(5)(6)(7)(8). A variety of radiopharmaceuticals including the 68 Ga-labelled PSMA inhibitor Glu-NH-CO-NH-Lys(Ahx)-HBED-CC have been widely studied as imaging probes for PET and been shown to increase detection of prostate cancer in patients with biochemical recurrence (9,10) and in patients with new diagnosis of prostate cancer (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, PSMA PET/CT is changing the 44 approach to recurrent PCa evaluation and management 45 [13,14]. high-risk (HR) PCa are limited [15][16][17][18][19]. In this study, we…”
mentioning
confidence: 98%